Knowledge, Attitude, and Practice towards Labor Pain Management and Associated Factors among Skilled Birth Attendants Working at Hospitals Found in Central, West, and North Gondar Zones, Northwest Ethiopia, 2019: A Multicenter Cross-Sectional Study. (15th May 2021) - Solomon, Eyasu Tekile; Kassie, Fisseha Yetwale; Mekonnen, Dawit Gebeyehu; Mihret, Muhabaw Shumye; Abate, Addisu Taye; Dessie, Amanuel Addisu
Abstract : Introduction . Delivery of the infant into the arms of a conscious and pain-free mother is the most exciting and rewarding moment in maternal care services. Physical and mental care of women during delivery requires good knowledge and a positive insight to the needs and rights of the mothers. Little was known regarding skilled birth attendants' knowledge, attitude, and practice towards labor pain management in the study area. Hence, the current study aimed at assessing knowledge, attitude, and practice, and associated factors towards labor pain management among skilled birth attendants working at hospitals found in central, west, and north Gondar zones, northwest Ethiopia, 2019. Method . A multicenter institution-based cross-sectional study was conducted from June 1 to 30, 2019. A census sampling technique was used to include a total of 336 skill birth attendants. A pretested standardized self-administered questionnaire was used to collect the data. The data were then entered into Epi Info 7.1.2 and exported to SPSS version 25 for analysis. Multivariable logistic regression analyses were undertaken to identify factors associated with outcome variables. The level of significance of the study was declared based on adjusted odds ratio with 95% confidence interval at a p value of ≤0.05. Result . The proportion of skill birth attendants having good knowledge, a favorable attitude, and a good practice on labor pain relief methods was 47%, 41.96%, and 57.14%, respectively. Age of ≤30 years (AOR = 5.43; 95% CI: 1.25, 23.53), educational status of 2 nd degree and above (AOR = 3.56; 95% CI: 1.32, 9.60), working at a private primary hospital (AOR: = 6.55; 95% CI: 2.15, 19.93), and working at a referral hospital (AOR = 2.24 : 95% CI: 1.01, 4.93) are factors significantly associated with good knowledge while having good knowledge on labor pain relief methods (AOR = 2.26; 95% CI: 1.42, 3.60) and working at private primary hospitals (AOR = 7.01; 95% CI: 1.92, 25.65) had statistically significant association with favorable attitude and good practice on labor pain relief methods, respectively. Conclusion and Recommendations . Poor knowledge, unfavorable attitude, and poor practice towards labor pain management were found in this study. Strengthening the capacity of public health facilities and providing continuous professional development (CPD) training for the skilled birth attendants would be helpful in improving knowledge, attitude, and practice towards labor pain management.